Indonesia's Capital Market Reaction During The Announcement Of Large-Scale Social Restrictions (Psbb) Volume Ii On Manufacturing Companies Listed On The Indonesia Stock Exchange - Khairul Azwar; Elly Susanti; Juan Anastasia Putri; Supitriyani (CV. Inara, 2021)
Since the beginning of the year, the index's performance Combined Share Price (JCI) Tends to decrease and experience Some fluctuations. Some sentiments Affects the movement of JCI. Moment The first two cases of Covid-19 were discovered. On March 2, for example, the price The stock fell 1.68 percent. In fact, down. deeper to 4.9 percent at 23 March in line with concerns market about the spread of the virus [1]. This study aims to determine the difference between Abnormal Return (AR) and Trading Volume Activity (TVA) before and after the Covid-19 pandemic in manufacturing companies listed on the Indonesia Stock Exchange. The research was conducted in manufacturing companies registered with 98 companies from September 2020 to October 2020. Data analysis in this study uses different test paired sample t-test, with the study's results showing an insignificant difference in abnormal return before and after the announcement of PSBB I (Large-Scale-Social Restrictions II). At the same time, there are significant differences before and after the announcement of PSBB I for trading volume activity. The results of this study can have implications for investors and potential investors as a source of information in decision making when investing and as a guideline to conduct an analysis of capital market performance as a basis for choosing companies that can provide large returns when important events such as the Covid-19 case occur.